2016
DOI: 10.1186/s12865-016-0163-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression levels of Ifi genes is associated to the increased resistance to spontaneous arthritis disease in mice deficiency of IL-1RA

Abstract: BackgroundThe mouse strain BALB/c deficient in IL-1 receptor antagonist protein (Il-1ra) develops spontaneous arthritis disease (SAD) while the strain DBA/1 IL1rn-/- with the same deficiency does not. Previously, we mapped a QTL on chromosome 1 for SAD and then developed a congenic mouse strain BALB.D1-1-/- that contains the QTL genomic fragment associated with resistance from DBA/1-/- on a BALB/c-/- background. The congenic strain was relatively resistant to spontaneous arthritis and had delayed onset and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Lefty1 encodes a secreted ligand of the TGF-beta superfamily of proteins 43 . A gene expression comparison between the congenic Bagg Albinos D1-1 (BALB.D1-1) mice and the parental BALB/c À/strain revealed that Lefty1 was down-regulated in the congenic strain in joint tissue, which is relatively resistant to spontaneous arthritis 44 .…”
Section: Osteoarthritis Andcartilagementioning
confidence: 99%
“…Lefty1 encodes a secreted ligand of the TGF-beta superfamily of proteins 43 . A gene expression comparison between the congenic Bagg Albinos D1-1 (BALB.D1-1) mice and the parental BALB/c À/strain revealed that Lefty1 was down-regulated in the congenic strain in joint tissue, which is relatively resistant to spontaneous arthritis 44 .…”
Section: Osteoarthritis Andcartilagementioning
confidence: 99%
“…By focusing on transcription factors with putative relevance to the polarization of monocytes towards classically activated M1 or alternatively activated M2 macrophages, we found that during infection with L. monocytogenes , the activation and development of proinflammatory monocytes is characterized by factors, such as Irf1, Irf2, Ifi204, Batf2, Mndal, and Irf7 [ 24 , 25 , 26 , 27 , 28 ] ( Figure 3 A). By contrast, during E. histolytica infection, Ly6C hi monocytes are characterized by the upregulation of transcription factors Mafb, Hes1, Fos, and Tsc22d3 ( Figure 3 A), which contribute to an anti-inflammatory and regenerative phenotype [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, some genes were differentially regulated, e.g., Arg1/Arg 2 , further suggesting an ongoing polarization into an anti-inflammatory M2 phenotype. In contrast, monocytes from the L. monocytogenes infection model were characterized by a classical proinflammatory, interferon-driven transcription factor-like profile (i.e., Mndal , Ifi204 and Irf2 ) [ 25 , 28 ], pointing towards an M1 phenotype [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their report, Alunno et al showed that high levels of circulating IFI16 in RA are more frequent in RF/anti-CCP-positive RA patients and significantly associated with pulmonary involvement. Most recently, a study using the IL-1RA-deficient mouse model found that decreased expression levels of Ifi genes were associated with increased resistance to SAD [ 10 ]. In addition, previously, interferon-inducible protein-10 (IP-10) was found to be linked to RA, although it is not located in the human HIN-200 cluster [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%